ENHANCEMENT IN THE PHOTOCATALYTIC ACTIVITY OF TiO2-ZnO NANOCOMPOSITES SYNTHESIZED BY MICROWAVE ASSISTED METHOD - M.B, SUWARNKAR; A.S, KIRDANT (Innovare Journal of Sciences, 2020)
Objective: To develop a new class of natural fiber based polymer composites to explore the potential of coir fiber, Rice Husk and Saw Dust. To fabricate the different composite by varying the fiber fraction and matrix fraction. To fabricate the hybrid composite by using coir fiber, Rice Husk and Saw Dust as a reinforcement and Unsaturated poly propylene as a matrix material. The present work reports on study of TiO2-ZnO photocatalyst with different ZnO content which is prepared via a microwave assisted method. This is simple, ecofriendly, an energy efficient and cost effective method. Materials and Methods: The 99% purity of titanium tetra-isopropoxide (TTIP), 99% purity of zinc nitrate, 99% purity of surfactant Cetyltrimethylammonium bromide and Sodium dodecyl sulphate (Spectrochem Pvt. Ltd., India), absolute ethanol (99.9%), ammonia. Result: Structural mechanism is closely related to the crystallite structure, which has been studied by using XRD technique. The X-ray diffraction patterns of various ratios of TiO2/ZnO composites. In the sample ‘T’ determined characteristics 2θ values and [hkl] planes are 25.06 [101], 37.59 [004], 48.01 [200], 62.31 [204] ascribed to reflections of anatase TiO2 which is comparable with JCPD Card No. (21-1272) Conclusion: TiO2-ZnO nano particles have been prepared by energy competent, cost efficient and an ecofriendly microwave assisted method.